An exploration into how Educational Psychologists (EPs) engage in culturally responsive practice through the consultative model of service delivery - Marriott, Holly (2023)
The Educational Psychologists (EPs) role involves working with Children and Young People (CYP), their families and professionals from a variety of cultural backgrounds. As with many school-based practices, a lack of cultural responsiveness can contribute to adverse outcomes for students from diverse backgrounds (McKenney, Mann, Brown, & Jewell, 2017). It has been argued that existing educational psychology assessment tools may be biased due to their lack of familiarity and cultural context, producing inaccurate results (Ardila, 2007; Reynolds & Suzuki, 2013). EPs are therefore responsible for participating in and developing culturally responsive practices to ensure the best possible outcomes for the society in which they provide services to.